Epistemologi Kritisisme Immanuel Kant Bagi Pengembangan Hukum Ekonomi Syariah - Sirojudin Munir, Akhmad (PT. ALHAFI BERKAH INDONESIA, 2023)
This research aims to answer the question by examining the impact of Immanuel Kant's epistemologi on the development of sharia economic law research. The method used is a literary method that is closely related to the research object, and is analyzed using philosophical and historical methods. This research found that Kant's critical philosophy began by questioning rationalist philosophy which accepted previous knowledge without criticizing it. Kant attempted to formulate an epistemological theory that would make a priori knowledge acceptable. Until finally, Kant discovered that knowledge is an a priori synthesis, between rationalism and empiricism. Thus, Kant's epistemologi creates urgency in developing the study of sharia economic law which seeks to form ideas about the importance of combining ideology and theory, between normative-idealist and historical-empirical. So that Islamic teachings can be applied in sharia economic law, especially in sharia financial institutions.